The link between left atrial longitudinal reservoir strain and mitral apparatus geometry in patients with dilated cardiomyopathy. (3rd October 2022) - Toader, D M; Mirea, O; Craciun-Mirescu, A; Magareata, G; Florescu, D; Iordache, S; Iovanescu, M; Cirstea, I; Aniculesei, A; Busu, M; Istratoaie, O; Militaru, C
Abstract: Background: 4-Dimensional Automated Left Atrial Quantification (4D Auto LAQ) is a technique that uses 3D volume data to determine LA strain. 4-Dimensional Automated Mitral Valve Quantification (4D Auto MVQ) evaluates anatomical and functional mitral valve parameters. Our study evaluated patients with dilated cardiomyopathy and tried to find a correlation between LA strain and mitral apparatus geometry. Methods: We enrolled 61 patients with dilated cardiomyopathy and 25 healthy volunteers. The evaluation consisted of clinical examination, laboratory tests, 12 leads electrocardiography. All participants underwent a complete transthoracic echocardiogram to determine cardiac structure and function according to the current guidelines. Measurement of LA strain and MV was performed using 4D Auto-quantification software. The study evaluated longitudinal strain during reservoir phase (LASr) and the parameters of the MV geometry that could interfere with left atrial function: annulus area, annulus perimeter, anteroposterior (A-P) diameter, posteromedial-anterolateral diameter (PM-AL), (the longest diameter of MV perpendicular to AP diameter); commissural diameter (CD), inter-trigonal distance, tenting height, tenting area, and tenting volume. Results: 1. The patients were divided in two groups: 26 with ischemic dilated cardiomyopathy and 35 with non-ischemic dilated cardiomyopathy. 2. Mean values of MV parameters in patients with dilated cardiomyopathy compare with healthy volunteers were: annulus area: 19.46 cm 2 vs 11.85 cm 2 ; annulus perimeter: 16.86 cm vs 12.71cm, A-P diameter 4.53 cm vs 3.45 cm, PM-AL diameter 4.84 cm vs 3.92 cm, CD 4.83 cm, vs 3.94 cm, inter-trigonal distance 3.9 cm vs 2.9 cm, tenting height 1.64 cm vs 1.05 cm, tenting area 4.82 cm 2 vs 1.78 cm 2, tenting volume 13.49 ml vs 4.27 ml. For LASr, mean values were 10.26 in patients with dilated cardiomyopathy vs 32.14 in healthy volunteers. Mean values of mitral valve parameters and LASr were comparable in ischemic vs non-ischemic cardiomyopathy patients. 3. LASr correlated with anatomical mitral valve parameters: annulus area: r=−0.6, annulus perimeter: r=−0.57, AP diameter: r=−0.58, PM-AL diameter: r=−0.58, commissural diameter: r=−0.66, inter-trigonal distance: r=−0.57, tenting height r=−0.53, tenting area r=−0.55 and tenting volume r=−0.54. Conclusions: 1. In patients with dilated cardiomyopathy phenotype, anatomical parameters of the mitral valve and LASr were altered. Results did not reveal significant differences between ischemic and non-ischemic etiology. 2. A correlation was found between the decrease in LASr and anatomical parameters of the mitral valve, suggesting a link between atrial function deterioration and deformity of mitral apparatus geometry in patients with dilated cardiomyopathy. Funding Acknowledgement: Type of funding sources: None.